2010
DOI: 10.1158/1078-0432.ccr-09-2890
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific FBXW7 Mutation and MYCN Copy Number Gain in Wilms' Tumor

Abstract: Purpose: Wilms' tumor (WT), the most common pediatric renal malignancy, is associated with mutations in several well-characterized genes, most notably WT1, CTNNB1, WTX, and TP53. However, the majority of cases do not harbor mutations in these genes. We hypothesized that additional drivers of tumor behavior would be contained within areas of consistent genomic copy number change, especially those associated with the WT risk groups defined by the International Society of Paediatric Oncology (SIOP).Experimental D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 43 publications
8
63
1
1
Order By: Relevance
“…High expression and copy number gain of MYCN have been associated with Wilms' tumor for a long time (Nisen et al 1986;Norris et al 1988;Williams et al 2010), and, recently, mutations in MYCN were identified by exome sequencing (Rakheja et al 2014), including a recurrent mutation (P44L) previously identified in neuroblastoma and believed to be a gain-of-function mutation . MYCN is a target of ubiquitination and degradation by FBXW7, which is deleted or mutated in ;4% of tumors .…”
Section: Wilms' Tumor Geneticsmentioning
confidence: 99%
“…High expression and copy number gain of MYCN have been associated with Wilms' tumor for a long time (Nisen et al 1986;Norris et al 1988;Williams et al 2010), and, recently, mutations in MYCN were identified by exome sequencing (Rakheja et al 2014), including a recurrent mutation (P44L) previously identified in neuroblastoma and believed to be a gain-of-function mutation . MYCN is a target of ubiquitination and degradation by FBXW7, which is deleted or mutated in ;4% of tumors .…”
Section: Wilms' Tumor Geneticsmentioning
confidence: 99%
“…We have recently described focal deletions that include the FBXW7 gene on 4q31.3 in postchemotherapy epithelial-type tumors (Williams et al, 2010). We examined the individual profiles of AH samples in which some degree of 4q loss was measured on the 32k platform for evidence of specific events at this locus.…”
Section: Copy Number Analysis Of Anaplastic Wilms Tumorsmentioning
confidence: 99%
“…Significant discriminator genes have also been identified in a study that compared 8 high risk tumors, including four with anaplasia, with 52 intermediate risk samples (Zirn et al, 2006). In a study of 104 tumors, we have recently shown that diffuse anaplasia is associated with MYCN gain in samples profiled at resection after a course of neoadjuvant chemotherapy (Williams et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Hypermethylation of this gene has also been observed in pediatric brain tumors and Wilms' tumors and in ovarian cancers that displayed chemotherapeutic resistance (25,27,28). Although these cancers are biologically different from neuroblastoma, amplification of the proto-oncogenes, such as c-myc, MYCN, or L-myc have been observed in a small proportion of these tumors (29)(30)(31), suggesting a possible interaction between proto-oncogenes and methylation that may contribute to the tumorigenesis of these cancers.…”
Section: Discussionmentioning
confidence: 99%